(untitled) (New York, N.Y., 2004)
Compacted into only about 1,100 pages, this book covers all aspects of manufacturing: planning, processes, quality assurance, experiments, economics, marketing, management, etc.
Công nghệ và thiết bị tạo phôi
Keywords: Production engineering